'The right way to be a woman': Negotiating femininity in a prison-based drug treatment programme. (January 2019) - Kolind, Torsten; Bjønness, Jeanett
Drawing from an ethnographic study in a drug treatment wing for women in a Danish prison, the authors explore how femininity is negotiated between prisoners and staff. It is shown how the staff view the prisoners as both passive and disruptive and how the treatment aims to teach them what staff consider to be an 'appropriate' femininity characterised by the women being cooperative, feeling a sense of community, and being less masculine in their appearance. While the prisoners accept the identity constructions imposed upon them by the therapy regime, they also attempt to create alternative femininities. The article discusses whether gender-sensitive treatment approaches can work towards better integration of the women's past experiences with the new dispositions learned in the treatment programme.